Review of SKUs in the Indian Paint Industry - Pandey, Devendra Kumar (Indian Journal of Marketing, 2013)
A stock-keeping unit or SKU is a unique identifier for each distinct product that can be purchased. SKUs are used in data management, enabling the company to systematically track its inventory or product availability. Each SKU is attached to a Product, Shade and Pack Size. The Decorative or architectural segment (which constitutes upto 70% of the total paint market) involves a very wide choice in terms of products, shades and pack sizes. In addition to this, in order to offer innovative products, companies are continuously offering newer shades to match the colour of carpets/curtains etc. Initially, these shades are produced in anticipation and once the market accepts these shades, they are produced regularly. While Industrial Paints are available in bulk packs of 20lt and 200lt, decorative paints are available in 20lt, 10lt, 4lt, 1lt, 500ml, 200ml, 100ml and 50ml packs. Enamel category alone has got around 720 SKUs. The combination of different products, shades and packs sizes resulted in over 2500 SKUs for Asian Paints. Through a survey of paint dealers, effort has been made to analyze the reasons for accumulation of slow moving stock, and the solutions adopted by the dealers to liquidate these stocks. The paper concludes by suggesting remedies to deal with high inventory cost and a large number of SKUs.